Effect of quick lime and superphosphate additives on emergence and survival of Rumex obtusifolius seedlings in acid and alkaline soils contaminated by As, Cd, Pb, and Zn - M. Hejcman; S. Vondráčková; V. Müllerová; K. Červená; J. Száková; P. Tlustoš (Plant, Soil and Environment, 2012)
Rumex obtusifolius is a troublesome weed widely spread in temperate grasslands and can be potentially used for detection of soils contaminated by trace elements. We asked how emergence and survival of its seedlings are affected by application of quick lime (Ca) and superphosphate (P) additives in soils contaminated by trace elements. We performed the pot seeding experiment with slightly acid Litavka soil contaminated by arsenic (As), cadmium (Cd), lead (Pb), and zinc (Zn) and alkaline Malín soil contaminated by As, Cd, and Zn. We used a control without any additives, Ca and P treatments in both soils. Higher and quicker emergence, together with substantially higher mortality of seedlings, was recorded in Litavka than in Malín. A positive effect of the Ca treatment on seedlings was recorded in Litavka, but a negative in Malín. Small seedlings with narrow and long leaves of reddish colour were recorded in Litavka in the control and in the P treatment both with high availability of Zn, Cd, and Pb. In the Ca treatment, leaves of seedlings were more elliptic and less reddish. In Malín, seedlings were green and substantially more vital in the control and in the P treatment than in Litavka. In the Ca treatment, small and unviable seedlings were recorded. Seedlings of R. obtusifolius are sensitive on high availability of Ca, Zn, Cd, and Pb in the soil.